Diastolic and autonomous dysfunction linked to heterogeneous myocardial repolarization and arrhythmia risk in patients with arterial hypertension and left ventricular hypertrophy - A. P. Ivanov; E. A. Sayeda; I. A. Elgardt; N. S. Sdobnyakova (Российский кардиологический журнал)
To assess the role of left ventricular (LV) diastolic dysfunction (DD), autonomous nervous system (ANS) and P wave changes on ECG, reflecting heterogeneous myocardial repolarization and LV hypertrophy (LVH) in arterial hypertension (AH), the results of echocardiography, Holter monitoring and P wave dispersion analysis were compared in 47 AH patients and 15 controls. Cardiac rhythm disturbances were assessed separately for impaired relaxation and restrictive variants of DD. Most arrhythmias were typical for restrictive DD only, which could be explained by greater atrial and ventricular myocardial changes in this group. These patients were also characterised by severe ANS dysfunction, manifested in increased sympathetic activation and reduced vagal influence, as well as in predominant central regulation of heart rate. Restrictive DD was also associated with substantial increase in P wave dispersion, reflecting heterogeneous repolarization in atrial myocardium. Consequently, arrhythmia risk in patients with AH and LVH is mostly related to electro-mechanical heart remodelling and ANS dysfunction.